ChemInform Abstract: Direct Catalytic C—H Arylation of Imidazol[1, 2‐a]pyridine with Aryl Bromides Using Magnetically Recyclable Pd—Fe3O4 Nanoparticles. Issue 46 (24th October 2013) - Lee, Jaewoo; Chung, Jooyoung; Byun, Sang Moon; Kim, B. Moon; Lee, Chulbom
Abstract The reaction is highly regioselective and no other regioisomer is obtained.